General Diaz Process, Industrial Diaz (American International Journal of Biology and Life Sciences, 2019)
According to general essential  of colorant  of azo  derivatives  and  structure, releasing  the substitution of the azo components  by  electron attracting groups produces required activity  enables to get    blue shades from structures .